The microwave adsorption behavior and microwave-assisted heteroatoms doping of graphene-based nano-carbon materials - Tang, Pei (Nature Publishing Group, 2014)
Microwave-assisted heating method is used to treat graphite oxide (GO), pyrolytic graphene oxide (PGO) and hydrogen-reduced pyrolytic graphene oxide (HPGO). Pure or doped graphene are prepared in the time of minutes and a thermal deoxygenization reduction mechanism is proposed to understand their microwave adsorption behaviors. These carbon materials are excellent catalysts in the reduction of nitrobenzene. The defects are believed to play an important role in the catalytic performance.